The belief on 'dedicatory devotion' in Hindu religious literature - Krishanhiny, T. (Eastern University, Sri Lanka & Sri Sathya Sai University, 2023)
The anxiety to know about one's future had been deep-rooted among Hindus from ancient times. For this purpose, various practices have been followed. These included observation of first sight, listening to indications, Astro - consultations, looking for the graceful sight of deities, and palm reading. Out of these, devotional contact is only one practice followed within the aforesaid 'observation of first sights' before one set out on some venture. In ancient Tamil literature, this had been a belief-oriented habit, seen as a policy of mental discipline. As a continuation of this at a stage when mental discipline was exerting its influence in Hindu literature too, devotional discipline appears to have been practiced seeing a favorable omen at a dubious situation as to whether one could reach God or not through his devotion contact. Such a belief has been expounded in Hindu literary works such as Thevaram, Thirukkovayar, Nalagira Divya Prabandham, and Kailaipathi Kalathipathi.
Keywords: Hindu Religious Literature; Believes; Dedicatory Devotion